Meningkatkan Kualitas Pembelajaran Guru Kelas I SDN Segugus Khanthil Kecamatan Borobudur Melalui Kegiatan “In House Traning” - Dwi Waluya (Jurnal Pendidikan Dasar, 2020)
Abstract. The objectives to be achieved in this study are the objectives to be achieved in this study is to determine the efforts to improve the quality of learning for grade I teachers of SDN Segugus Khanthil, Borobudur District through In House Traning activities. The research subjects in this study were ten teachers. The main data were obtained from informants such as school principals and teachers. Data collection methods by interview, observation, and documentation methods.The results showed that in-house training activities with a discussion and interaction approach were able to improve the quality of learning for grade 1 teachers atSD Negeri Gugus Khanthil, Borobudur Magelang sub-district in the quality of learning in the 2019/2020 school year. In terms of quality before giving actions in the form of in-house training activities, the teacher's ability in learning quality competencies reached a percentage of 51.67%. After being given the action, it increased in cycle I by 66.25% and in cycle II increased to 85.83%. In terms of quantity before giving the action in the form of in-house training the number of teachers who were able to improve the quality of their learning reached a percentage of 40%. After being given the action, it increased in cycle I by 80% and in cycle II increased to 100.00%.